Effect of implant‐supported prosthesis on the bite force and masticatory efficiency in subjects with shortened dental arches. (21st December 2013) - Meena, A.; Jain, V.; Singh, N.; Arora, N.; Jha, R.
Summary The aim of the study was to assess changes in bite force and masticatory efficiency in shortened dental arch (SDA) subjects rehabilitated with implant‐supported restoration for 1st molar. Ten SDA subjects with bilaterally missing mandibular molars (experimental group) were recruited. In each subject, one tapered threaded implant was placed bilaterally in 1st mandibular molar region and restored. Masticatory efficiency was evaluated objectively by measuring the released dye from chewed raw carrots, with a 'spectrophotometer' at 530 nm preoperatively and at 3 months after restoration. Bite force was evaluated using 'bite force measuring appliance' preoperatively, at 6 weeks and at 3 months after restoration. Ten completely dentate‐matched subjects (in terms of age, sex, height and weight) acted as control. The results revealed that as compared with the control group, the experimental group showed significantly less (P < 0·05) mean maximum bite force at pre‐restoration and at 6 weeks after restoration. Although at 3 months the mean maximum bite force value was less than the control group but the mean difference was statistically insignificant. The mean difference of masticatory efficiency between control and experimental group was statistically significant (P < 0·05) before restoration, but was statistically insignificant at 3 months after restoration. Thus it was concluded that after the restoration of mandibular arch with implant‐supported prosthesis, both bite force and masticatory efficiency of all SDA subjects increased and were comparable to that of matched completely dentate subjects after 3 months.